Role of animal models in understanding the mechanisms of autoimmune diseases - Wasif N. Khan; Grace M. Lacoume; Eric L. Greidinger (Autoimmunity)
Autoimmune diseases are diverse, necessitating a mechanistic understanding of the protracted disease process to improve diagnostic accuracy and therapeutic efficacy. From human and animal model studies, it has become clear that T cells are critical for autoimmune pathogenesis but the involvement of B cells is unmistakable, as evidenced by the efficacy of B cell depletion therapy in alleviating systemic and organ-specific autoimmune conditions. This paper reviews the roles that kinds of murine models have played and continue to play in developing mechanistic understanding of autoimmune diseases, with particular though not exclusive attention to B cells emphasizing their unique contributions to autoimmunity via adaptive and innate mechanisms.